Synthesis of 3'-deoxy-3'-(18F)fluoro-thymidine with 2,3'-anhydro-5'-O-(4,4'-dimethoxytrityl)-thymidine - Wodarski, Christine; Eisenbarth, Joseph; Weber, Klaus-Josef; Henze, Marcus; Haberkorn, Uwe; Eisenhut, Michael (Journal of labelled compounds and radiopharmaceuticals, 2000)
[11C]Thymidine has been used as a proliferation marker in positron-emission-tomography (PET) studies of tumors. This compound showed metabolite related problems and the radiosynthesis proved to be difficult. Recently, the more stable 3′-deoxy-3′-[18F]fluorothymidine ([18F]FLT) has been suggested as an alternative. One advantage of [18F]FLT is based on thymidine kinase-1 catalyzed phosphorylation of FLT and the intracellular accumulation of this metabolite without participation in DNA synthesis. The radiosynthesis of [18F]FLT originally designed by Grierson et al. was found to be demanding especially regarding the workup of the [18F]fluoride/1-(2-deoxy-3-O-nosyl-5-O-DMT-β-D-threo-pento-furanosyl)-3-DMBn-thymine reaction mixture. Instead, we used 2,3′-anhydro-5′-O-(4,4′-dimethoxytrityl)thymidine as a precursor for the synthesis of [18F]FLT. In DMSO at 175°C and in presence of Kryptofix® 2.2.2. we obtained 5.6± 1,4% [18F]FLT (EOS). Copyright © 2000 John Wiley & Sons, Ltd.